2012
DOI: 10.1371/journal.pone.0051182
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Kinship and MHC Class II Genotype on Visual Traits in Zebrafish Larvae (Danio rerio)

Abstract: Kin recognition can drive kin selection and the evolution of social behaviour. In zebrafish (Danio rerio, Hamilton 1822), kin recognition is based on olfactory and visual imprinting processes. If larvae are exposed to visual and chemical cues of kin at day 5 and 6 post fertilization they will recognize kin throughout life, while exposure to non-kin fails to trigger any recognition. Chemical imprinting signals are transcribed by polymorphic genes of the major histocompatibility complex (MHC) code; however, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Finally, orthologs of mammalian vasopressin and oxytocin, whose functions are linked to motivated social behaviors, are expressed in larvae at around 5 days post-fertilization (Herget et al, 2014; Caldwell and Albers, 2015). Intriguingly, around this stage, larvae begin to express olfactory guided social recognition, hinting at the possible functional involvement of these neuropeptides (Gerlach et al, 2008; Hinz et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Finally, orthologs of mammalian vasopressin and oxytocin, whose functions are linked to motivated social behaviors, are expressed in larvae at around 5 days post-fertilization (Herget et al, 2014; Caldwell and Albers, 2015). Intriguingly, around this stage, larvae begin to express olfactory guided social recognition, hinting at the possible functional involvement of these neuropeptides (Gerlach et al, 2008; Hinz et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…In addition to olfaction, many nonhuman species also rely upon visual signals for kin recognition [38]. Studies of zebrafish, for example, have shown that family-specific morphometry and pigmentation patterns are all influenced by MHC genotype [26]. These visual cues are useful signals for kin recognition in zebrafish [26].…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish larvae exposed to kin at day 5 and 6 days post-fertilisation recognise each other throughout their life, due to a combination of visual and olfactory imprinting. This process involves the major histocompatibility complex (MHC) code, which influences the chemical and visual features that zebrafish display [37]. Zebrafish appear to only imprint upon kin expressing similar MHC class II genes, and this process is likely olfactory based, because MHC peptides can activate a subset of neurons in the olfactory bulb [38 ].…”
Section: Social Behaviourmentioning
confidence: 99%